ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA MASYARAKAT SEKITAR TAMAN NASIONAL BUKIT BARISAN SELATAN KABUPATEN PESISIR BARAT - M. Reza Fachrezy; Zainal Abidin; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to determine the socio-economic characteristics of farmers, analyze the income structure, the factors that affect the income of farmers, and the level of household welfare of farmers who live around Bukit Barisan Selatan National Park, Pesisir Barat District. This research is a survey research involving 99 respondents who were randomly selected. Respondents were spread across four subdistricts, namely Bengkunat Belimbing, Ngambur, Pesisir Selatan, and Karya Penggawa Districts. The study was conducted from July to August 2018. The first objective was analyzed qualitatively, the second objective was analyzed using household income analysis, the third objective used multiple linear regression analysis, and the fourth objective was using Sajogyo's criteria (1997). The study suggested that the socio-economic characteristics of the farmers around TNBBS were spread from 15 to 64 years of age with an average age of 43.74 years. The average education level was elementary school, the number of majority of family sizes was from 4 to 6 people (67.68%), and the average land was 1.41 ha. The average household income of farmers is IDR 36,946,883.94 per year, which consists of on-farm income 63.68%, off-farm income 11.00%, and non-farm income 25.33%.. Factors that affect farmers' income are fertilizer costs and labor costs. The welfare of farmers around TNBBS is in quite prosperous category.Key words: characteristics, household income, welfare